180k views
5 votes
Write an exponential function y = abx for a graph that includes (–4, 72) and (–2, 18).

User Ashleen
by
4.9k points

2 Answers

0 votes

ANSWER


y = (9)/(2) ( { (1)/(2) })^(x)

EXPLANATION

Let the exponential function be


y = a {b}^(x)

Since the graph includes (–4, 72), it must satisfy this equation.


72= a { b}^( - 4)

Multiply both sides by b⁴ .

This implies that,


a = 72 {b}^(4) ...1

The graph also includes (-2,18).

We substitute this point also to get:


18=a {b}^( - 2)

Multiply both sides by b²


a = 18 {b}^(2) ...(2)

We equate (1) and (2) to obtain:


72 {b}^(4) = 18 {b}^(2)

Multiply both sides by


\frac{72 {b}^(4) }{ {18b}^(4) } = \frac{18 {b}^(2) }{18 {b}^(4) }


4 = \frac{1}{ {b}^(2) }

Or


{2}^( 2) = ( (1)/(b) )^(2)


(1)/(b) = 2


b = (1)/(2)

Put b=½ into equation (2).


a = 18 {( (1)/(2) })^(2)


a = (18)/(4)


a = (9)/(2)

Therefore the equation is


y = (9)/(2) ( { (1)/(2) })^(x)

User Praneybehl
by
5.4k points
5 votes

Answer:


y=4.5(0.5)^(x)

Explanation:

* Lets revise the meaning of exponential function

- The form of the exponential function is
y=ab^(x),

where a ≠ 0, b > 0 , b ≠ 1, and x is any real number

- It has a constant base b

- It has a variable exponent x

- To solve an exponential equation, take the log or ln of both sides,

and solve for the variable

* Lets solve the problem

∵ y = a(b)^x is an exponential function

∵ Its graph contains the point (-4 , 72) and (-2 , 18)

- Lets substitute x and y by the coordinates of these points

# Point (-4 , 72)


y=ab^(x)

∵ x = -4 and y = 72


72=ab^(-4)

- The change any power from -ve to +ve reciprocal the base of

the power (
p^(-n)=(1)/(p^(n))


72=(a)/(b^(4))

- By using cross multiplication


a=72b^(4) ⇒ (1)

# Point (-2 , 18)

∵ x = -2 and y = 18


18=ab^(-2)


18=(a)/(b^(2))

- By using cross multiplication

∴ a = 18b² ⇒ (2)

- Equate the two equations (1) and (2)


72b^(4)=18b^(2)

- Divide both sides by 18b²


(72b^(4))/(18b^(2))=4b^(4-2)=4b^(2)


(18b^(2))/(18b^(2))=(1)b^(2-2)=(1)b^(0)=(1)(1)=1

∴ 4b² = 1 ⇒ divide both sides by 4


b^(2)=(1)/(4)=0.25 ⇒ take square root for both sides

∴ b = √0.25 = 0.5

- Lets substitute the value ob b in equation (1) or (2) to find a

∵ a = 18b²

∵ b² = 0.25

∴ a = 18(0.25) = 4.5

- Lets substitute the values of a and b in the equation
y=ab^(x)


y=4.5(0.5)^(x)

- We can write it using fraction


y=(9)/(2)((1)/(2))^(x)

User Khundragpan
by
5.1k points